Afro-communitarianism and the nature of reconciliation - Oelofsen, Rianna (Rhodes University, Faculty of Humanities, Department of Philosophy, 2013)
In this dissertation I sketch a conception of personhood as understood from within an Afrocommunitarian worldview, and argue that this understanding of personhood has implications for understanding the concept of reconciliation. Understanding 'being human' as a collective, communal enterprise has implications for how responsibility, justice, forgiveness and humanization (all cognate concepts of reconciliation) are conceptualized. In line with this understanding of reconciliation and its cognate concepts, I argue that the humanization of self and other (according to the Afrocommunitarian understanding of personhood) is required for addressing the 'inferiority' and concurrent 'superiority' racial complexes as diagnosed by Franz Fanon and Steve Biko. These complexes reach deeply within individual and collective psyches and political identities, and I argue that political solutions to protracted conflict (in South Africa and other racially charged contexts) which do not address these deeply entrenched pathologies will be inadequate according to an Afrocommunitarian framework.
Keywords: Ubuntu (Philosophy); Reconciliation -- South Africa; Communitarianism -- Africa; Philosophy, African